Cigarette smoking and rate of gastric emptying: effect on alcohol absorption. Issue 6767 (5th January 1991) - Johnson, R D; Horowitz, M; Maddox, A F; Wishart, J M; Shearman, D J
Abstract : OBJECTIVE--To examine the effects of cigarette smoking on alcohol absorption and gastric emptying. DESIGN--Randomised crossover study. SETTING--Research project in departments of medicine and nuclear medicine. SUBJECTS--Eight healthy volunteers aged 19-43 who regularly smoked 20-35 cigarettes a day and drank small amounts of alcohol on social occasions. INTERVENTIONS--Subjects drank 400 ml of a radiolabelled nutrient test meal containing alcohol (0.5 g/kg), then had their rates of gastric emptying measured. Test were carried out (a) with the subjects smoking four cigarettes an hour and (b) with the subjects not smoking, having abstained for seven days or more. The order of the tests was randomised and the tests were conducted two weeks apart. MAIN OUTCOME MEASURES--Peak blood alcohol concentrations, absorption of alcohol at 30 minutes, amount of test meal emptied from the stomach at 30 minutes, and times taken for 50% of the meal to leave the proximal stomach and total stomach. RESULTS--Smoking was associated with reductions in (a) peak blood alcohol concentrations (median values in non-smoking versus smoking periods 13.5 (range 8.7-22.6) mmol/l v 11.1 (4.3-13.5) mmol/l), (b) area under the blood alcohol concentration-time curve at 30 minutes (264 x 10(3) (0-509 x 10(3)) mmol/l/min v 140 x 10(3)) (0-217 x 10(3) mmol/l/min), and (c) amount of test meal emptied from the stomach at 30 minutes (39% (5-86%) v 23% (0-35%)). In addition, smoking slowed both the 50% gastric emptying time (37 (9-83) minutes v 56 (40-280) minutes) and the intragastric distribution of the meal. There was a close correlation between the amount of test meal emptied from the stomach at 30 minutes and the area under the blood alcohol concentration-time curve at 30 minutes (r = 0.91; p less than 0.0001). CONCLUSION--Cigarette smoking slows gastric emptying and as a consequence delays alcohol absorption.